2017
DOI: 10.1007/s11695-017-2982-1
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Bariatric Surgery Publications and Global Productivity: A Bibliometric Analysis

Abstract: The present study shows that the studies on BS has mainly been conducted in developed and developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 34 publications
6
26
0
Order By: Relevance
“…However, developing countries, led by Turkey, such as India, China, and Iran had a notable effect on article productivity. Some bibliometric research in the literature determined that the economic size of a country, or development level, had a significant effect on academic publication productivity [5,[13][14][15][16][17][18][19][20][21][22]24]. In our study, the significant correlation results found between the number of articles produced by countries and certain development indicators confirm the results of the literature.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, developing countries, led by Turkey, such as India, China, and Iran had a notable effect on article productivity. Some bibliometric research in the literature determined that the economic size of a country, or development level, had a significant effect on academic publication productivity [5,[13][14][15][16][17][18][19][20][21][22]24]. In our study, the significant correlation results found between the number of articles produced by countries and certain development indicators confirm the results of the literature.…”
Section: Discussionsupporting
confidence: 88%
“…A limitation of our study is that only the WoS database was used for literature scanning. Databases like PubMed, Google Scholar, and Scopus were not used, because the WoS database indexes articles published in journals with a higher impact factor compared to the other databases [5,24]. Additionally, in situations where more than one database is used for bibliometric studies analyzing large numbers of articles, the inclusion of the same article more than once in the analysis may affect the reliability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Then we used CiteSpace V (64 bits) to analyze publication outputs and construct knowledge maps. In addition, we also used software VOSviewer (version 1.6.6) for better network visualizations in some cases ( Ozsoy & Demir, 2017 ; Van Eck & Waltman, 2010 ). In this paper, the individual network was derived from the 50 most cited articles published in a one-year time slice.…”
Section: Methodsmentioning
confidence: 99%
“…It is a quantitative method based on the analysis of the publications about a topic. [11][12][13] The value of bibliometric analyses increases in line with the increase in the number of publications in literature because sometimes a bibliometric analysis performed with thousands of publications enables to reveal the latest trends, collaboration between authors, and active journals about a specific topic, which helps researchers to save time in literature review. [14][15][16] Despite the fact that NEC is one of the reasons for morbidity and mortality in the newborn intensive care units, the literature indicates no bibliometric studies that made a holistic evaluation of the publications on this issue.…”
Section: Introductionmentioning
confidence: 99%